PENINGKATAN KESEJAHTERAAN KELOMPOK USAHA PETANI JAGUNG DESA SAENTIS MELALUI PRODUKSI LIMBAH BONGGOL JAGUNG - Hrp, Ardhansyah Putra; Supiyandi, Supiyandi; Andriana, Melly; Siregar, Ina Namora Putri (Abdi Laksana : Jurnal Pengabdian Kepada Masyarakat, 2020)
The purpose of PKM activities is to help solve the problems of partners to become independent and lead to a productive economy by utilizing corncob waste. The PKM partner is corn farmers in Desa Saentis which is ± 25 km or 40 minutes from UMN Al-Washliyah. The partner priority issues are ; (1) aspects of production, including; a) partners do not have the knowledge and skills in processing corncobs; b) partners never to training processing corncobs from the government or the private sector; c) partners donâ€™t have the appropriate technology to process corncobs into handicraft items. (1) aspects of production, including: a) Focus Group Discussion on the potential of corn waste into handicraft items; b) the use of appropriate technology in the form of grinding machines and hacksaw to make handicrafts from corncobs; c) Benchmarking partners corn cob crafter; and d) training to design handicraft made from corn cobs. Output targets include: 1) grinding machines and hacksaw; 2) enhancing partner skills in the production of handicraft items made from corn cobs; 3) design of handicraft made from corn cobs such as tissue boxes, decorative lamps, placemats.